2021
DOI: 10.1016/j.cie.2021.107593
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based assessment of supply chain resilience with consideration of recovery strategies in the COVID-19 pandemic context

Abstract: In the wake of the COVID-19 pandemic, many firms lacked a strategy to cope with disruptions and maintain resiliency. In this study, we develop a measurement method to evaluate the impact of resilience strategies in a multi-stage supply chain (SC) in the presence of a pandemic. For the first time, we propose a method to deduce quantitative resilience assessment from simulation. We implement two resilience strategies, i.e., prepositioning extra-inventory and a backup supplier, and then we simulate its impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 68 publications
0
41
0
9
Order By: Relevance
“…These strategies of the case studies in Thailand can be confirmed by Belhadi et al (2021), stating that localisation of supply sources is the best strategy to mitigate risks related to supply chain resilience during the coronavirus epidemic in the automotive industry. Moosavi and Hosseini (2021) found that extra inventory resulted in a higher resilience than a backup supplier. However, the companies require to absorb the greater cost.…”
Section: New Normal Within Automotive Businessesmentioning
confidence: 99%
See 2 more Smart Citations
“…These strategies of the case studies in Thailand can be confirmed by Belhadi et al (2021), stating that localisation of supply sources is the best strategy to mitigate risks related to supply chain resilience during the coronavirus epidemic in the automotive industry. Moosavi and Hosseini (2021) found that extra inventory resulted in a higher resilience than a backup supplier. However, the companies require to absorb the greater cost.…”
Section: New Normal Within Automotive Businessesmentioning
confidence: 99%
“…However, the COVID-19 pandemic differs from natural disasters or human-made interruptions (Guan et al, 2020). The duration and magnitude of the coronavirus outbreak (the scope of the disruption's impact on related enterprises) are catastrophic compared to other experienced disruptions (Moosavi & Hosseini, 2021). The knowledge and BCP transferred from partners were the fundamental measures in overcoming the risk related to the pandemic.…”
Section: Technology Transfer From Supply Chain Partners and The Experiences From Past Crisis Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…( Ivanov and Dolgui, 2020 ) stated that complex networks in the SC have become more fragile due to severe disruptions such as pandemics that alter the structures and dynamics of the SC. Further, the simulation techniques such as system dynamics modelling allow developing a variety of resilience measure plans, considering severe interruptions ( Moosavi & Hosseini, 2021 ). Therefore, to help businesses, these approaches are integrated with complexity theories to investigate the impact of COVID-19 on the resilience of countries.…”
Section: Introductionmentioning
confidence: 99%
“…The design of resilient chains for MSEs must consider these complexities because these companies have important contributions in regional development due to their local character and history [14]. This fact has been magnified due to the pandemic of COVID-19 that has generated a great impact in supply chains both in magnitude (scale of the impact) and duration (length of the impact) [15]. Thus, the resilience of supply chains has become important considering the local disturbances that can spread upstream and downstream affecting the entire chain.…”
Section: Introductionmentioning
confidence: 99%